2016
DOI: 10.1111/1753-6405.12532
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced surveillance of a lymphogranuloma venereum outbreak in Sydney 2010–2012

Abstract: Objectives: To investigate an increase in lymphogranuloma venereum (LGV) notifications in New South Wales (NSW).Methods: Enhanced surveillance of notified LGV cases in NSW between May 2010 and April 2012 using doctor and patient questionnaires.Results: Thirty-seven doctors who had diagnosed 67 (76%) of 88 notified anorectal LGV infections were interviewed. The majority (n=33, 89%) of treating doctors were formally trained and accredited in HIV management and prescribing, and most (n=32, 86%) worked in a public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…In the present study, LGV2b (ST58) was isolated from three patients and ST108 from a third, demonstrating the global spread of these virulent strains. The ongoing epidemic of biovar L2b that was first identified in the Netherlands in 2003, mainly among HIV-positive MSM (Nieuwenhuis et al, 2004;Nieuwenhuis et al, 2003;Spaargaren et al, 2005), has spread globally to other industrialized countries (Martin-Iguacel et al, 2010;Kendall et al, 2014;Cabello Ubeda et al, 2016;Parra-Sanchez et al, 2016;Templeton et al, 2016;Isaksson et al, 2017;Latini et al, 2017). This is the first report of this biovar in Israel.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, LGV2b (ST58) was isolated from three patients and ST108 from a third, demonstrating the global spread of these virulent strains. The ongoing epidemic of biovar L2b that was first identified in the Netherlands in 2003, mainly among HIV-positive MSM (Nieuwenhuis et al, 2004;Nieuwenhuis et al, 2003;Spaargaren et al, 2005), has spread globally to other industrialized countries (Martin-Iguacel et al, 2010;Kendall et al, 2014;Cabello Ubeda et al, 2016;Parra-Sanchez et al, 2016;Templeton et al, 2016;Isaksson et al, 2017;Latini et al, 2017). This is the first report of this biovar in Israel.…”
Section: Discussionmentioning
confidence: 89%
“…Researchers have also studied the variety of MSM subculture(s) in relation to anal intercourse without condom, HIV and other STIs [81][82][83][84][85][86] . Certain places and contexts (e.g.…”
Section: Adventurism Sensation Seeking and Msm Subculturesmentioning
confidence: 99%
“…Still, men living with HIV risk being reinfected with drug-resistant HIV virus strains 126 . Further, the risk of STI transmission remains for MSM regardless of HIV status, and the risk of STIs has been shown to be high among sexually adventurous MSM 83 and in networks tied to specific venues among MSM 183 . This complexity alters the prevention landscape and stresses the need for strengthening MSMs' ability to talk about HIV status, ART status/viral loads and PrEP use with sex partners.…”
Section: Anal Intercourse and Riskmentioning
confidence: 99%
“…Outbreaks of lymphogranuloma venereum (LGV) leading to ulcerative proctitis have persisted in Australia for over a decade among MSM populations [27][28][29][30]. Whilst most of these infections are of an anorectal nature, recent cases of LGV had a clinical presentation of penile ulcers [30].…”
Section: Sexually Transmitted Ct Infections-sti Infections With No Inmentioning
confidence: 99%
“…In general, recent data on prevalence of anorectal Ct infections indicates that these are common, particularly in MSM populations, with diagnosis rates continuing to rise and symptoms diversifying. This is of an increasing public health concern as use of pre-exposure prophylaxis (PrEP) against HIV becomes commonplace in this subpopulation [27,29]. Other subpopulations are also at higher risk than others-data indicated that anorectal Ct infections are present in women and may be more common than anorectal Neisseria gonorrhoeae infections [31], with certain populations such as female sex workers at higher risk [32].…”
Section: Sexually Transmitted Ct Infections-sti Infections With No Inmentioning
confidence: 99%